2011
DOI: 10.4103/1596-3519.82061
|View full text |Cite
|
Sign up to set email alerts
|

A review of stroke admissions at a tertiary hospital in rural Southwestern Nigeria

Abstract: Stroke is also a common neurological condition in rural Nigeria, in view of the fact that almost 70% of the patients had ≥2 risk factors of stroke. We recommend that, sustainable, community-friendly intervention programmes are incorporated into the health care system for the early prevention, recognition, and modification of the risk factors in persons prone to the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
60
7
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 23 publications
(48 reference statements)
31
60
7
1
Order By: Relevance
“…3,4 Stroke is defined as a syndrome of rapidly developing clinical symptoms and signs of focal (or global) loss of cerebral functions, with symptoms lasting 24 hours or longer or resulting in death with no apparent cause other than of vascular origin 5 . The prevalence of stroke in Nigeria is on the increase.6, 7 Osuntokun et al6 reported a crude prevalence of 58 per 100,000 of the population and Danesi et al 7 in a more recent studies reported a rate of 1.14 per 1,000. It is principally a disease of the elderly 8 however there is an increase in the prevalence of stroke in younger age group 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Stroke is defined as a syndrome of rapidly developing clinical symptoms and signs of focal (or global) loss of cerebral functions, with symptoms lasting 24 hours or longer or resulting in death with no apparent cause other than of vascular origin 5 . The prevalence of stroke in Nigeria is on the increase.6, 7 Osuntokun et al6 reported a crude prevalence of 58 per 100,000 of the population and Danesi et al 7 in a more recent studies reported a rate of 1.14 per 1,000. It is principally a disease of the elderly 8 however there is an increase in the prevalence of stroke in younger age group 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for the high burden of stroke are linked to the high rates of chronic hypertension, type 2 diabetes mellitus (T2DM), excessive alcohol intake, smoking, insufficient fruit and vegetable consumption [6][7][8] , sickle cell disease, HIV infection and even antiretroviral drugs 9 . Also, ischemic stroke is more suffered than hemorrhagic stroke 10,11 . A large part of Africa as Central Africa was not included in the Interstroke Study phase 1, and a systematic evaluation of the risk factors in various ethnic groups and geographical locations is an effective global strategy to reduce the risk of premature stroke 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In two other crosssectional, hospital-based studies conducted during 2001 and 2006-2008 in Qom, a well-known religious city of Iran, the casefatality rate within the first month was reported at 24.6% during 2001, and at 15.3% from 2006 to 2008. Although, these figures showed an apparently declining rate over time in this region, but were still greater than reported ones from western countries and lesser than other developing countries [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 61%